Material Analysis of Al-Hiwar and Al-Qira'ah on Arabic Text-books for Senior High School Grade 10 MGMP East Java Based on Curriculum of Ministry of Education, Culture, Research, and Technology - Linda Ayu Khuroidah; Mirwan Akhmad Taufiq; Mochammad Indra Yumanto (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
Textbooks have an essential role in the success of the learning process, as well as teaching materials in learning Arabic. Selecting the correct text is the primary key to implementing the curriculum. This study examines the suitability of the Arabic student book for 10th grade of SMA (Senior High School) by Subject Teacher Conference (MGMP) East Java to the curriculum of the ministry of education and culture, focusing on Al-Hiwar and Al-Qira'ah materials. This study used a qualitative approach. It was analyzed using content analysis techniques according to the perspective of Abdur Rohman bin Ibrahim Al Fauzi with the primary source material Al-Hiwar and Al-Qira'ah from the Arabic student book for 10th grade of SMA by MGMP East Java and other documentation sources as secondary data. The results of the research have found that the Arabic student book for 10th grade of SMA by MGMP East Java based on the 2017 Ministry of Education and Culture curriculum is explained as follows; first, the suitability of the Al-Hiwar and Al-Qira'ah materials to the curriculum can be seen in the appropriate social, spiritual, and cognitive values ​​contained in the material. Second, Al-Hiwar's material is under the intellectual power of students, far from linguistic errors and the meaning of life. Third, the lack of good quality scores on the variation of questions (At-Tadribat) on Al-Hiwar and Al-Qira'ah material, no clear indicators or instructions according to the Theme, and no pictures are provided on Al-Hiwar or Al-Qira'ah material. So from the results of this analysis, it is necessary to revise the Arabic student book for the 10th grade of SMA by MGMP East Java. Keywords: Text Analysis, Arabic Textbook, Arabic Writing Skills, Arabic Reading Skills, Learning Arabic. Abstrak Buku pelajaran memiliki peran penting dalam keberhasilan proses pembelajaran, begitu juga dengan bahan ajar dalam pembelajaran bahasa Arab. Memilih teks yang benar adalah kunci utama untuk mengimplementasikan kurikulum. Kajian ini mengkaji tentang kesesuaian buku siswa bahasa Arab kelas X SMA oleh Musyawarah Guru Mata Pelajaran (MGMP) Jawa Timur dengan kurikulum Kementerian Pendidikan dan Kebudayaan, dengan fokus pada Al-Hiwar dan Al-Qira'ah. Penelitian ini menggunakan pendekatan kualitatif. Dianalisis menggunakan teknik analisis isi menurut perspektif Abdur Rohman bin Ibrahim Al Fauzi dengan sumber utama materi Al-Hiwar dan Al-Qira'ah dari buku siswa bahasa Arab kelas X SMA oleh MGMP Jawa Timur dan sumber dokumentasi lainnya sebagai data sekunder. Hasil penelitian menemukan bahwa buku siswa bahasa Arab Kelas X SMA Karya MGMP Jawa Timur Berdasarkan Kurikulum Kementerian Pendidikan dan Kebudayaan Tahun 2017 dijelaskan sebagai berikut; pertama, kesesuaian materi Al-Hiwar dan Al-Qira'ah dengan kurikulum dapat dilihat dari kesesuaian nilai-nilai sosial, spiritual, dan kognitif yang terkandung dalam materi tersebut. Kedua, materi Al-Hiwar berada di bawah daya intelektual siswa, jauh dari kesalahan bahasa dan makna hidup. Ketiga, Kurangnya skor kualitas yang baik pada variasi soal (At-Tadribat) pada materi Al-Hiwar dan Al-Qira'ah, tidak ada indikator atau petunjuk yang jelas sesuai tema, dan tidak disediakan gambar pada Al-Hiwar maupun Al-Qira'ah. Maka dari hasil analisis tersebut, perlu adanya revisi buku siswa bahasa Arab kelas X SMA oleh MGMP Jawa Timur. Kata Kunci: Analisis Teks, Buku Teks Bahasa Arab, Keterampilan Menulis Bahasa Arab, Keterampilan Membaca Bahasa Arab, Pembelajaran Bahasa Arab.